Creative Dance in Elementary Schools: A Theoretical and Practical Justification - Mac Donald, Colla (Canadian Journal of Education/Revue canadienne de l’éducation, 1991)
This article presents a theoretical and practical justification for the inclusion of creative dance in the elementary school curriculum, using findings of a study in which I examined the effects of six creative-dance workshops on elementary school teachers’ attitudes to and practices of creative dance. The study found that teachers’ attitudes and practices changed as a result of the workshops and that children enjoy and benefit from creative-dance activities. Teachers’ reflections on their experiences show that creative dance has a vital role in the elementary school curriculum and illustrate the close relationship between theoretical and practical aspects of creative dance. Cet article présente une justification théorique et pratique de l’intégration au programme du primaire de l’expression corporelle, justification faisant appel aux conclusions d’une étude dans laquelle l’auteur se penche sur les effets de six ateliers d’expression corporelle sur les attitudes des enseignants au primaire à l’égard de l’expression corporelle et sur les pratiques de ceux-ci en la matière. L’étude révèle que les attitudes et les pratiques des enseignants changent à la suite de ces ateliers et que les enfants prennent plaisir à ces activités et en tirent parti. Les réflexions des enseignants sur leurs expériences indiquent que l’ex- pression corporelle a un rôle clé à jouer au primaire et illustrent les rapports étroits qui peuvent être établis entre les aspects théoriques et pratiques de l’expression corporelle.